2015
DOI: 10.1038/srep13393
|View full text |Cite
|
Sign up to set email alerts
|

Social, spatial and temporal organization in a complex insect society

Abstract: High-density living is often associated with high disease risk due to density-dependent epidemic spread. Despite being paragons of high-density living, the social insects have largely decoupled the association with density-dependent epidemics. It is hypothesized that this is accomplished through prophylactic and inducible defenses termed ‘collective immunity’. Here we characterise segregation of carpenter ants that would be most likely to encounter infectious agents (i.e. foragers) using integrated social, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…Importantly, behavioural and physiological processes may be linked through host–parasite feedbacks (Ezenwa et al., ; Gudelj & White, ; VanderWaal & Ezenwa, ). An important next step for spatial, individual‐based models might be to incorporate feedbacks between behaviour and physiology, such as sickness‐induced behavioural changes or variable transmission efficiency between populations (Croft et al., ; Ezenwa et al., ; Quevillon, Hanks, Bansal, Hughes, & Gordon, ; Wilson et al., ). Advances in the field of ecoimmunology are making the data needed for such analyses ever more accessible (Adelman, Moyers, & Hawley, ).…”
Section: Future Directions: Addressing Global Challengesmentioning
confidence: 99%
“…Importantly, behavioural and physiological processes may be linked through host–parasite feedbacks (Ezenwa et al., ; Gudelj & White, ; VanderWaal & Ezenwa, ). An important next step for spatial, individual‐based models might be to incorporate feedbacks between behaviour and physiology, such as sickness‐induced behavioural changes or variable transmission efficiency between populations (Croft et al., ; Ezenwa et al., ; Quevillon, Hanks, Bansal, Hughes, & Gordon, ; Wilson et al., ). Advances in the field of ecoimmunology are making the data needed for such analyses ever more accessible (Adelman, Moyers, & Hawley, ).…”
Section: Future Directions: Addressing Global Challengesmentioning
confidence: 99%
“…motifs (Milo et al, 2002), which represent triadic patterns of connection between nodes in a directed network. Network motifs can be representative of various biological processes such as information flow (Nandi et al, 2014), resource exchange (Quevillon et al, 2015) or disease spread (Waters & Fewell, 2012). In a bee movement network, the analyses of network motifs might help to identify behavioural rules underpinning trapline formation ( Fig.…”
Section: Network Analysesmentioning
confidence: 99%
“…); and Quevillon et al . () demonstrated how interaction patterns between black carpenter ants ( Camponotus pennsylvanicus ) belonging to different functional grounds (foragers, nest ants, queen, etc.) could theoretically constrain pathogen transmission.…”
Section: Introductionmentioning
confidence: 99%
“…VanderWaal & Ezenwa 2016). For example, experimental contacts between desert tortoises (Gopherus agassizii) underscored the importance of contact quality in transmission of Mycoplasma agassizii (Aiello et al 2016); and Quevillon et al (2015) demonstrated how interaction patterns between black carpenter ants (Camponotus pennsylvanicus) belonging to different functional grounds (foragers, nest ants, queen, etc.) could theoretically constrain pathogen transmission.…”
Section: Introductionmentioning
confidence: 99%